Principal's Strategy in Developing the Character of Students at the Al-Mahir Surakarta Qur'an and IT Islamic Boarding School - Putra, Dutha Bahari Esa Tyas Kurtubi; Mujahid, Imam (Civilization Research: Journal of Islamic Studies, 2025)
The principal's strategy in shaping the leadership character of students is very important to prepare a generation of future leaders who are professional and trustworthy. This study aims to determine the planning, describe the implementation of the strategy and determine the evaluation of the principal's strategy to develop the leadership character of students at PPQIT Al-Mahir Surakarta. This writing uses primary data and is qualitative. The data source was obtained from the results of a case study from the PPQIT Al-Mahir Surakarta educational institution during one leadership period, namely the 2024-2025 academic year. The results of the study revealed that the principal's strategy to develop the leadership character of students at PPQIT Al-Mahir Surakarta is: (1) The principal makes plans by forming programs to develop the leadership character of students (2) in implementing the strategy, the principal optimizes the leadership character development program for students through forum meetings. (3) Evaluation of the principal's strategy for developing student leadership character by means of performance assessments to determine whether the program being implemented can develop the students' leadership character.